TIME-SERIES EXPANSION OF OIL PALM PLANTATION IN PULANG PISAU REGENCY - Suprojo, Baskara; Affandi, Muhamad Irfan (JURNAL GEOGRAFI Geografi dan Pengajarannya, 2024)
The primadonna of oil palm is unavoidable as the largest commercially cultivated crop in tropical regions, especially Indonesia. The escalation in oil palm demand aligns with Land Use Land Cover (LULC) conversion and the transformation of global agricultural landscape. Expansion in Kalimantan proves that the oil palm areas increased from 90,300 ha to 3,164,000 ha, with 90% of the converted land being forest areas. Complexity of these issues drives need to conduct research on oil palm plantation expansion in Pulang Pisau Regency. This study presents the manifestation of LULC conversion into oil palm plantations through remote sensing. The results show the expansion of oil palm plantations from 2009-2023, non-compliance with applicable spatial regulations, and changes in the agrarian structure of the surrounding communities. This analysis can serve as a decision-making tool for stakeholders in the oil palm sector that is effective and efficient in terms of cost, time, and effort. Keywords: Spatial Analysis, Oil Palm, Community, Government Regulation